Exploring in vitro expression and immune potency in mice using mRNA encoding the Plasmodium falciparum malaria antigen, CelTOS - Waghela, Ishita N.; Mallory, Katherine L.; Taylor, Justin A.; Schneider, Cosette G.; Savransky, Tatyana; Janse, Chris J.; Lin, Paulo J. C.; Tam, Ying K.; Weissman, Drew; Angov, Evelina (Frontiers in Immunology, 2022)
The secreted malarial protein, Cell-Traversal protein for Ookinetes and Sporozoites (CelTOS), is highly conserved among Plasmodium species, and plays a role in the invasion of mosquito midgut cells and hepatocytes in the vertebrate host. CelTOS was identified as a potential protective antigen based on a proteomic analysis, which showed that CelTOS stimulated significant effector T cells producing IFN-γ in peripheral blood mononuclear cells (PBMCs) from radiation attenuated sporozoite-immunized, malaria-naïve human subjects. In a rodent malaria model, recombinant full-length CelTOS protein/adjuvant combinations induced sterile protection, and in several studies, functional antibodies were produced that had hepatocyte invasion inhibition and transmission-blocking activities. Despite some encouraging results, vaccine approaches using CelTOS will require improvement before it can be considered as an effective vaccine candidate. Here, we report on the use of mRNA vaccine technology to induce humoral and cell-mediated immune responses using this antigen. Several pfceltos encoding mRNA transcripts were assessed for the impact on protein translation levels in vitro. Protein coding sequences included those to evaluate the effects of signal sequence, N-glycosylation on translation, and of nucleoside substitutions. Using in vitro transfection experiments as a pre-screen, we assessed the quality of the expressed CelTOS target relative to the homogeneity, cellular localization, and durability of expression levels. Optimized mRNA transcripts, which demonstrated highest protein expression levels in vitro were selected for encapsulation in lipid nanoparticles (LNP) and used to immunize mice to assess for both humoral and cellular cytokine responses. Our findings indicate that mRNA transcripts encoding pfceltos while potent for inducing antigen-specific cellular cytokine responses in mice, were less able to mount PfCelTOS-specific antibody responses using a two-dose regimen. An additional booster dose was needed to overcome low seroconversion rates in mice. With respect to antibody fine specificities, N-glycosylation site mutated immunogens yielded lower immune responses, particularly to the N-terminus of the molecule. While it remains unclear the impact on CelTOS antigen as immunogen, this study highlights the need to optimize antigen design for vaccine development.